The Influence of Work Compensation and Work Motivation on Employee Performance - Rohaeni, Heni; Wijayanti, Murti; Baeshak Tomaluweng, Jamyan; Ridwan, Ridwan; Wahyu Setyowati, Novita (Dinasti Publisher, 2024)
This study aims to determine how much influence work compensation and work motivation have on employee performance. The population in this study were all production. This research uses quantitative methods. Collecting data by distributing questionnaires (questionnaire) to 85 respondents, the sampling method in this study was to use a saturated sample, so the total sample was taken, namely 85 employees. The results of this study indicate that the Work compensation variable has no partial and significant effect, with the calculated t value greater than t table and the Work Motivation variable has a partial effect, with the calculated t value greater than t table. Based on the results of the simultaneous F test, the calculated F value was F table with a sig. or a significant value less than 0.05. There fore H0 is rejected or Ha is accepted, which means that simultaneously Work compensation and Work Motivation have a significant effect on Employee Performance.